Design Model for Yoga Industry Development in Indonesia - Arifin, Safrin; Ayuningtyas , Dumilah; Nurhasana , Renny; Mustofa , Budiman M; Akbar , Bintang Mukhammad Burhanudin; Subu , Muhammad Arsyad (Journal of Ecohumanism, 2024)
The yoga industry is part of wellness tourism and a mainstay for development in Indonesia. This is due to the encouragement of achieving health security targets, sustainable development goals, and economic advancement. This condition encourages the need to develop a development model to give the yoga industry a competitive edge. The data collection process uses the Penta helix to obtain comprehensive, detailed, and precise information. The data obtained is then processed using the Soft system method approach. The results show that the yoga industry has excellent potential to be developed with the support of several important things: Policy, Brand Image, Communication, Flexibility, Local Wisdom, and Trust. On the other hand, the development process requires a roadmap and continuous performance measurement.